Model Pentahelix Dalam Pengembangan Kawasan Konservasi Penyu Berbasis Ekowisata di Ampiang Parak Kabupaten Pesisir Selatan - Coirala, Fillia Agustin (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Indonesia is rich in biodiversity, one of which is turtles. Turtles in the world are included in Appendix Cites 1. This is because turtles are rare animals whose populations are almost extinct. This extinction is because there are still many people who have not been able to carry out turtle conservation activities and there is still rampant hunting for turtles to be used as food, souvenirs, and for traditional ceremonies. Indonesia is a country visited by 6 of the 7 turtle species in Indonesia, but in 1999-2000 the peak of the largest massacre occurred at Tanjung Benoa Bali. Awareness of turtle conservation and the environment requires the synergy of many stakeholders. Nagari Ampiang Parak is a central area for turtle conservation in West Sumatra, and has succeeded in conducting ecotourism-based turtle conservation. The purpose of this research is to find out the stakeholders involved from the government, private sector, media, academia and society. As well as analyzing the synergy of each stakeholder involved. The research method used is descriptive qualitative, with data collection through observation, interviews and document review. Informants in this study are groups of each element of the stakeholders. The result of this research is that in the ecotourism-based turtle conservation area in Nagari Ampiang Parak, the pentahelix model is applied, namely the involvement of academia, private sector, government, community and media. These five stakeholders synergize with each other by implementing 4 forms of communication between stakeholders, namely downward communication, upward communication, lateral communication and diagonal communication. As well as coordinating with each other but not optimal enough because 2 of the 9 coordination requirements are only carried out by a few stakeholders, namely initial opportunities and simple organization. And it was found that the element that has the strongest role in the management of this turtle conservation area is the Ampiang Parak LPPL(Laskar Pemuda Peduli Lingkungan) community because it was initiated directly by the community and they are the direct managers of the area.